Droits et voix / Rights and Voices : La Criminologie - Veronique Strimelle (Les Presses de l'Université d'Ottawa | University of Ottawa Press, 2010)
This volume commemorates the 40th anniversary of the University of Ottawa's Department of Criminology, founded in 1968. It relates the history of the department from its origins to today, focusing on the theoretical debates that have influenced its critical and self reflexive approach to criminology. The contributions to this volume continue in that vein by questioning the traditional perspective of criminology on a variety of topics including police studies, mental health, political violence, suicide, and crime prevention. Rights and Voices reveals the significant role that the University of Ottawa has played in redefining criminology to advocate activism, social justice, and compassion.